2013
DOI: 10.1371/journal.pone.0061106
|View full text |Cite
|
Sign up to set email alerts
|

Flight Performance and Feather Quality: Paying the Price of Overlapping Moult and Breeding in a Tropical Highland Bird

Abstract: A temporal separation of energetically costly life history events like reproduction and maintenance of the integumentary system is thought to be promoted by selection to avoid trade-offs and maximize fitness. It has therefore remained somewhat of a paradox that certain vertebrate species can undergo both events simultaneously. Identifying potential costs of overlapping two demanding life history stages will further our understanding of the selection pressures that shape the temporal regulation of life history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…Birds undergoing primary feather moults typically associated with annual complete moults have high energy demands and are compromised in their ability to fly; consequently, this activity is usually undertaken when and where resources are high (Echeverry‐Galvis & Córdoba‐Córdoba, ; Echeverry‐Galvis & Hau, ). We interpret higher probabilities of capturing individuals undergoing active primary moults as an indication of better performance in a habitat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Birds undergoing primary feather moults typically associated with annual complete moults have high energy demands and are compromised in their ability to fly; consequently, this activity is usually undertaken when and where resources are high (Echeverry‐Galvis & Córdoba‐Córdoba, ; Echeverry‐Galvis & Hau, ). We interpret higher probabilities of capturing individuals undergoing active primary moults as an indication of better performance in a habitat.…”
Section: Methodsmentioning
confidence: 99%
“…Since breeding‐related activities such as incubation and food provisioning are energy demanding, their timing and location are typically constrained by resource availability (Echeverry‐Galvis & Córdoba‐Córdoba, ; Echeverry‐Galvis & Hau, ). We interpret a higher probability of capturing individuals with evidence of active breeding as an indication of better performance in a habitat.…”
Section: Methodsmentioning
confidence: 99%
“…This is highlighted by several studies where feather moult has been shown to be traded against competing energydemanding processes, such as reproduction, migration and pre-migratory fuel accumulation (e.g. Rubolini et al, 2002;Echeverry-Galvis and Hau, 2013;Saino et al, 2014). Energy is required for feather keratin and pigment synthesis, for buffering the temporary loss of insulation during body feather replacement, and (in the case of flight feather moult) to compensate for the reduced foraging efficiency due to impaired mobility (Murphy, 1996).…”
Section: Moult Oxidative Status and Sex Differencesmentioning
confidence: 99%
“…The time required to produce quality replacement plumage, without significantly increasing daily costs (Hoye & Buttemer ), ultimately determines moult scheduling (Cornelius et al . , Echeverry‐Gavlia & Hau , Saino et al . , Kiat & Izhaki ).…”
mentioning
confidence: 99%